Impact of a cerebrospinal fluid diagnostic stewardship intervention on quantity of tests, length of stay, antibiotic prescriptions, and cost - Aaron Pathak; Sabra Shay; Todd Lasco; Mayar Al Mohajer (Antimicrobial Stewardship & Healthcare Epidemiology)
Redundant and low-value cerebrospinal fluid analysis for suspected meningitis can increase costs and antimicrobial use. Our diagnostic stewardship intervention limited available infectious disease cerebrospinal fluid assays to seven common tests, including a multiplex polymerase chain reaction panel. There was no significant difference in the cost of testing or clinical outcomes.